Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1021/acs.jpcc.2c00612
|View full text |Cite
|
Sign up to set email alerts
|

First-Principles Study of Oxygen-Induced Disintegration and Ripening of Late Transition Metal Nanoparticles on Rutile-TiO2(110)

Abstract: Under an industry-related high-temperature oxidation atmosphere, the structure and chemical states of metal nanocatalysts meeting sustainable development challenges change dramatically, deteriorating the activity and/or lowering the yield. Theoretically revealing the mechanisms of oxygen-induced structure evolution and establishing a framework to distinguish them are vital to improving the operando stability and rational design of metal nanocatalysts. Here, we studied the oxygen-induced disintegration and Ostw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 59 publications
(79 reference statements)
0
5
0
Order By: Relevance
“…Equation indicated that when migrating across the support surface, the mobile Ru(CO) n complexes could be “trapped” at the cost of isolated hydroxyls. According to Li and co-workers, both CO and O 2 were typical adsorbents that gave rise to adatom complexes with low diffusion barrierprecursors of the disintegration of supported metal nanoparticles (i.e., Δ G NP dis < 0 with X = CO or O 2 in eq ). By replacing the adsorbed CO atoms in eq with O atoms, the OH-Ru–O x interactions over CeO 2 could be presented in eq : Ru O x + Ce 3 + OH Ce 4 + O lattice 2 Ru O x + 1 / 2 H 2 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Equation indicated that when migrating across the support surface, the mobile Ru(CO) n complexes could be “trapped” at the cost of isolated hydroxyls. According to Li and co-workers, both CO and O 2 were typical adsorbents that gave rise to adatom complexes with low diffusion barrierprecursors of the disintegration of supported metal nanoparticles (i.e., Δ G NP dis < 0 with X = CO or O 2 in eq ). By replacing the adsorbed CO atoms in eq with O atoms, the OH-Ru–O x interactions over CeO 2 could be presented in eq : Ru O x + Ce 3 + OH Ce 4 + O lattice 2 Ru O x + 1 / 2 H 2 …”
Section: Resultsmentioning
confidence: 99%
“…The relatively high Ru dispersion of the as-received catalyst was evidenced by CO chemisorption (Table ) and was reconfirmed by the absence of Ru-related phases in the XRD pattern (Figure S3). To launch “oxidative redispersion” of the supported Ru nanoparticles, the as-received catalyst was calcined in an air flow (200 mL/min) at 300 °C for 1 ha proven strategy to produce single-site Ru species over CeO 2 . ,,, The thus-obtained sample (O300) did show a 1.6 times increased Ru dispersion (Table ), indicating that the disintegration of Ru nanoparticles occurred during the oxidation treatment. As illustrated in Table , such treatment did not lead to detectable Ru loss. Therefore, the redispersion process was more likely induced by Ru particle disintegration and surface atom migration rather than trapping of gaseous species like RuO 4 , which was in consistent with the results obtained by Liu et al Nevertheless, small Ru nanoparticles (with an average diameter of 1.3 nm) could still be found on the surface of O300 (Figure C), some of which were covered with oxide overlayers (see Figure D and Figure S4, probably corresponding to the Ru@RuO 2 core–shell structure , ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…TiO 2 has three crystal structures namely brookite, rutile, and anatase. The last two crystal structures are thermodynamically more stable [ 9 ] with the band gap energy (Eg) of ±3.0–3.2 eV. When compared to the rutile structure, the anatase TiO 2 phase structure has more excellent photo-catalytic properties including electron transfer rate that is 89 times greater, chemically and biologically inert, mechanical toughness, low cost and non-toxic [ 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%